Cone calorimetric studies on the mechanism of action of new fire-retardants used for polyester resins - Kicko-Walczak, E. (Polimery, 2022)
Cone calorimetry was used to carry out a complex analysis of the pyrolysis of selected glass-reinforced polyester laminates (GRPL) based on two compositions of unsaturated polyester resins (UPR) fire-nonretarded and fire-retarded and smoke suppressed by the use of mixtures of zinc hexahydroxystannate ZnSn(OH)6 and zinc borate or zinc molybdate. The heat release (average) rate (HRR and HRRav), time required to ignite a GRPL, the mass loss rate and (average) surface extinction area (SAE and SAEJV) were studied in relation to thermal irradiation power and to presence or absence of a fire retardant. The cone calorimeter is shown to enable all the stages of pyrolysis of GRPL involving combustion and smoke emission, to be analyzed. It was confirmed effective influence of the Sn/Zn systems as a fire retardans additive for polyester resins.